Factors influencing enrollments of high school students in the Nicolet College Automotive Technology program: what encourages enrollment and what eiscourages enrollment - Kolasa, Christopher J. (University of Wisconsin--Stout, 2018)
The purpose of this study was to identify factors that encourage or discourage the enrollment of high school student graduates in Nicolet College's Automotive Technology program. The results of the study found that students with higher levels of automotive knowledge and those that had access to professional mentors were more likely to consider further automotive education. Students with accurate conceptions of the work performed by automotive technicians were less likely to consider further automotive education. Automotive repair skill was not a significant factor in determining whether they pursue further automotive education. Lastly, a significant number of high school students are interested in automotive technology under the auspice of a hobby in contrast to a career. Given these findings, the automotive technology program should provide professional development that leads to Automotive Service Excellence (ASE) certification for area high school automotive instructors so they can become more effective mentors. It should also support high school students' avocational interests in automotive technology by holding workshops, sponsoring events, and connecting students with accomplished members of the car hobby as an indirect approach to the recruitment of high school students to Nicolet College's Automotive Technology program.
Keywords: High school students; Automobiles; Maintenance and repair; Mentoring; Nicolet College